Performance of drivers with Parkinson's Disease under the effect of cognitive overloading: insinuation for assessment and training - Chee, Derserri; Lee, Hoe; Lee, Andy; Falkmer, Torbjorn (Aracne Editrice, 2013)
Background: Signs and symptoms of Parkinson’s disease (PD) include a combination of slowness of movement, increased tone, tremor and loss of postural reflexes. Cognitive changes and dementia can also be found in older people affected by PD. The excessive expenditure of cerebral resources in multitasks can cause cognitive overload resulting in deterioration of functional performance. Previous research has highlighted that the balance of cognitive load is essential for safe driving; however, this has not yet been researched in relation to people with PD. Coupled with mental inflexibility and sluggish reasoning, PD drivers exposed to demanding traffic scenarios may reach dangerous levels of cognitive overload. The present study employed computation of arithmetic sums as secondary task to investigate the effect of cognitive overloading on older PD drivers. Methodology: A pre-post case-control study design was implemented. Convenience sample of 28 mild to moderate stages of PD drivers and 30 age-matched healthy controls were recruited and their motor and cognitive functions were assessed using the Digit Vigilance Test (DVT), Perdue Pegboard, Symbol Digit Modalities Test (SDMT) and Trail-Making Test- Part A and B. Participants were then assessed twice using a driving simulator: with and without exposure to the secondary task.Results: When compared with healthy controls, PD drivers scored lower in motor and cognitive psychometric assessments and performed less competently in driving assessments. However, PD drivers drove more cautiously and took more time to complete all the driving tests when compared with the healthy counterparts. With the distraction of the secondary task, both the performance of PD drivers and controls declined, but PD drivers to a greater extent. The Trail-Making Test-B was found to be valuable in predicting the overall performance of PD drivers. The ability of PD participants was observed to have significant deterioration in driving through T-junctions and roundabouts. Conclusion: PD drivers should avoid cognitive overload caused by, for example, multitasking while driving. Cognitive overload may compound the problem of indecisiveness of the drivers; leading to inconvenience or dangers to other road users. Training of PD drivers should emphasize intersection manoeuvre management.